(untitled) (Annals of Medical Research, 2021)
Aim: This study aimed at determining the effect of sociodemographic and obstetric characteristics of pregnant women on their anxiety levels. Material and Methods: Designed as a descriptive study, it was conducted in Obstetric polyclinics of a University Hospital located in Eastern Turkey. The study consisted of 793 pregnant women admitted to the specified obstetric polyclinics for follow-up from July 15th, 2018 to December 31st, 2018. Descriptive characteristics form and Spielberger’s State Anxiety Inventory-SAI were used in data collection. Results: The study determined that the educational level, parity, infertility treatment, complications during pregnancy and infections during pregnancy are important predictors of SAI score during pregnancy. (R=0.238, R2=0.057, F=9.432, p0.001).Conclusion: Study results demonstrated that educational level, parity, infertility treatment, complications during pregnancy and infection in the first trimester of pregnancy were significant predictors of anxiety